Effect of the fungus Metarhizumanisopliae (Metchnikoff) Sorokin and actelic insecticide in the protection of bean seeds packaged in bag from infection by cowpea beetle (Baghdad Science Journal, 2025)
this study was perform to defined the effect of fungus Metarhiziumanisopliae Sorokin with concentrations 5x101, 5x103 and 5x105 spore/ ml and Actelic insecticide with concentration 0.001% inin rate of germinate treated string bean seeds also study effect of packed bags in two different type: jute and polypropylene bags which treated with fungal suspension pervious mention and insecticide in rate infested the string bean seeds packed in it.Results of the study showed the following:Lower rate of weight loss of cowpea seeds appear in poly propylene bags 4.41, 5.95% after six months of treatment with 5x 105 spore/ ml and Actelic insecticide respectively compared with 15.08% to control treatment. The fungal concentrations and insecticide not effect Significantly in the rates of string bean germinate.